Interaction impact of drought stress, nutrient-deficient water, and seed-borne pathogen (Alternaria alternata) on germination and vigor of two tomato varietiesination and vigor of two tomato varieties - Y.T.N., Nhi; M., Massimi; L., Radócz (International Journal of Horticultural Science, 2024)
Tomato (Solanum lycopersicum) is considered one of the leading vegetable plants in the world. This study evaluated the germination and vigor capabilities of ‘Marmande’ and ‘Kecskeméti Jubileum’ varieties under different conditions, including drought stress, nutrient-deficient water, and the effect of seed-borne disease caused by Alternaria alternata when prime and non-prime with salicylic acid. The experiment was conducted in the laboratory in 2023 at Agricultural and Food Sciences and Environmental Management Faculty of University of Debrecen. Results indicated that the ‘Kecskeméti Jubileum’ variety exhibited a superior strength to ‘Marmande’ in the seedling’s dry weight, seedling growth rate, and vigor index under nutrient-deficient water. Nevertheless, when applying levels of drought, the ‘Marmande’ variety had a higher viability rate of 62.5% in comparison with another variety, and the germination rate of the two tomato varieties is at 85.5% in 5% concentration but decreased progressively when exposed to a higher drought concentration of 10%. When using 3 ml of salicylic acid during germination stages, the seedling vigor index of ‘Marmande’ shows a greater index at 165 compared to ‘Kecskeméti Jubileum’, just 108 under the infection of Alternaria alternata. The results of the examination of drought stress, and the effect of Alternaria alternata, one cause of seed-borne pathogens, showed that the percentage germination and vigor ability of the ‘Marmande’ variety performed better than ‘Kecskeméti Jubileum’ under the same conditions.